Topiramate use during pregnancy and major congenital malformations in multiple populations. Issue 4 (16th March 2015) - Tennis, Patricia; Chan, K. Arnold; Curkendall, Suellen M.; Li, De‐Kun; Mines, Daniel; Peterson, Craig; Andrews, Elizabeth B.; Calingaert, Brian; Chen, Hong Y.; Deshpande, Gaurav; Everage, Nicholas; Holick, Crystal N.; et al.
Abstract : Background: We measured birth prevalence of major congenital malformations (MCMs) after topiramate use during pregnancy to screen for a possible signal of increased risk. Methods: Using four healthcare databases, we identified three cohorts of pregnant women: cohort 1, used topiramate during the first trimester; cohort 2, used topiramate or another antiepileptic drug previously but not during pregnancy; and cohort 3, were pregnant and did not use topiramate but had indications for use individually matched to those of users. Cohort 1 was compared with cohorts 2 and 3. MCMs were a code for any major congenital malformation dated within 30 days of the delivery date on the mother's claims or within 365 days after infant birth date, excluding a genetic or syndromic basis, and with procedure or healthcare usage consistent with the MCM diagnosis code in the 365 days after infant birth. Results: Of the 10 specific common MCMs evaluated, 1 (conotruncal heart defects) had a prevalence ratio greater than 1.5 for both primary comparisons, and 4 (ventricular septal defect, atrial septal defect, hypospadias, coarctation of the aorta) had a prevalence ratio greater than 1.5 for one of the two comparisons. Following screening of organ systems with elevated MCMs, the prevalence ratio was greater than 1.5 for patent ductus arteriosus in both comparisons and for obstructive genitourinary defects in one comparison. Conclusion: To evaluate a large number of MCMs across many pregnancies, we used crude methods for detecting potential signals. Therefore, these results should be seen as potential signals, not causal. Birth Defects Research (Part A) 103:269–275, 2015. © 2015 Wiley Periodicals, Inc.